Application of the mercury porosimetry method in the analysis of sorption materials - R. K. Kostoev; D. S. Tochiev; E. I. Nilkho; Z. N. Sultigova; R. D. Archakova; B. A. Temirkhanov; L. Ya. Uzhakhova (Тонкие химические технологии)
Objectives. This study aims to establish the available porosity of a sorbent based on carbonized rice husk and investigate its sorption properties for oil and oil products.Methods. A rice-husk-based sorbent carbonized at 400°С for 30 min was selected as the subject. The porosity of this sorbent is analyzed with the help of mercury porosimeters, the Pascal 140 EVO and Pascal 240 EVO. The sorption properties of the sorbent are also studied when cleaning water containing oil and oil products.Results. The test sample is a bulk porous material with a pore volume of 0.015 cm/g; porosity higher than 15% was found, and the pore size distribution is shown. Studies were conducted on the sorption of oil and oil products as well as the possibility of using the aforementioned sorbent as a filtering material in the purification of water containing oil products. We investigated the sorption processes under dynamic and static conditions. The methodology for measuring the porous structure of solid materials on the mercury porosimeter, Pascal 140 EVO, was examined. The texture characteristics of the sorbent’s porous structure were determined, which is primarily the total volume of pores, the values of the specific surface area, and the volume of the microspores and mesopores.Conclusions. The materials studied can be used as sorbents with a developed porous structure for purification of water with dissolved and emulsified petroleum products.